T2/FLAIR Abnormity Could be the Sign of Glioblastoma Dissemination - Li, Mingxiao; Huang, Wei; Chen, Hongyan; Jiang, Haihui; Yang, Chuanwei; Shen, Shaoping; Cui, Yong; Dong, Gehong; Ren, Xiaohui; Lin, Song (Frontiers in Neurology, 2022)
Purpose Newly emerged or constantly enlarged contrast-enhancing (CE) lesions were the necessary sign for the diagnosis of glioblastoma (GBM) progression. This study aimed to investigate whether the T2/FLAIR abnormal transformation could predict and assess progression for GBMs, especially for tumor dissemination. Methods A consecutive cohort of 246 GBM patients with regular follow-up and sufficient radiological data was included in this study. The series of T2/FLAIR and T1CE images were retrospectively reviewed. The patients were separated into T2/FLAIR and T1CE discordant and accordant subgroups based on the initial progression images. Results A total of 170 qualified patients were finally analyzed. The incidence of discordant T2/FLAIR and T1CE images was 25.9% (44/170). The median time-span of T2/FLAIR indicated tumor progression was 119.5 days (ranging from 57 days-unreached) prior to T1CE. Nearly half of patients (20/44, 45.5%) in the discordant subgroup suffered from tumor dissemination, substantially higher than accordant patients (23/126, 20.6%, P<0.001). The median time to progression (TTP), post-progression survival (PPS), and overall survival (OS) were not statistically different (all P>0.05) between discordant and accordant patients. Conclusions T2/FLAIR abnormity could be the sign of GBM progression, especially for newly emerged lesions disseminating from the primary cavity. Physicians should cast more attention on the dynamic change of T2/FLAIR images, which might be of great significance for progression assessment and subsequent clinical decision-making.